2014
DOI: 10.1037/a0030962
|View full text |Cite
|
Sign up to set email alerts
|

The Authenticity Scale: Psychometric properties of a French translation and exploration of its relationships with personality and well-being.

Abstract: In this article, we examined the psychometric properties of a French translation of the Authenticity Scale created by A. M. Wood, P. A. Linley, J. Maltby, M. Baliousis, and S. Joseph (2008, The authentic personality: A theoretical and empirical conceptualization and the development of the authenticity scale, Journal of Counseling Psychology, 55, 385-399). In the first study (N ϭ 188), we assessed the reliability of this translation as well as its construct validity and discriminant validity from the Big Five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 53 publications
3
33
0
7
Order By: Relevance
“…Further, the authors demonstrated the hypothesized direction of the relations among the components, as well as the direction of the relations between each component and several indicators of well‐being. Other studies have bolstered the scale's validity (Vess, Schlegel, Hicks, & Arndt, ; White & Tracey, ), cross‐cultural reliability and validity (Robinson, Lopez, Ramos, & Nartova‐Bochaver, ), and factor structure (Grégoire, Baron, Menard, & Lachance, ; White, ).…”
Section: What Is Authenticity?mentioning
confidence: 99%
“…Further, the authors demonstrated the hypothesized direction of the relations among the components, as well as the direction of the relations between each component and several indicators of well‐being. Other studies have bolstered the scale's validity (Vess, Schlegel, Hicks, & Arndt, ; White & Tracey, ), cross‐cultural reliability and validity (Robinson, Lopez, Ramos, & Nartova‐Bochaver, ), and factor structure (Grégoire, Baron, Menard, & Lachance, ; White, ).…”
Section: What Is Authenticity?mentioning
confidence: 99%
“…The results of test-retest reliability in this research are low, statistically insignificant correlations which may indicate that during the 10-week period authenticity is unstable as a personality trait. Test-retest reliability of the original Authenticity Scale, as well as its adaptations, showed stability of authenticity as a personality trait during two weeks (Ilhan & Özdemir, 2013;Shamsi et al, 2012;Wood et al, 2008), and eight weeks (Grégoire et al, 2014). Also, the majority of female participants (93%) strongly influence the gender structure of the sample and might affected these results of test-retest reliability.…”
Section: Reliabilitymentioning
confidence: 99%
“…Internal consistency of the subscale Authentic living is acceptable and equals to α = .68 for the initial, and α = .63 for the retest measuring. Original subscales Authentic living, Accepting external influence and Self-alienation showed internal consistency as follows: .62, .67 and .79 (Wood et al, 2008), in Iranian adaptation .82, .81 and .77 (Shamsi et al, 2012), in French adaptation between .77 and .82 (Grégoire et al, 2014), and in Turkish adaptation .62, .67 and .79 (Ilhan & Özdemir, 2013). The results confirm the internal consistency of the scale.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The Authenticity Scale appears to have good psychometric properties. To the best of our knowledge, there are several adaptation of this instrument -Iranian [6], Turkish [7], French [8] and Serbian [9]. All adaptations of the Authenticity Scale showed that the instrument in question is reliable and valid.…”
Section: Introductionmentioning
confidence: 99%